The KISS Principle in Survey Design: Question Length and Data Quality. Issue 1 (August 2016) - Alwin, Duane F.; Beattie, Brett A.
Writings on the optimal length for survey questions are characterized by a variety of perspectives and very little empirical evidence. Where evidence exists, support seems to favor lengthy questions in some cases and shorter ones in others. However, on the basis of theories of the survey response process, the use of an excessive number of words may get in the way of the respondent's comprehension of the information requested, and because of the cognitive burden of longer questions, there may be increased measurement errors. Results are reported from a study of reliability estimates for 426 (exactly replicated) survey questions in face-to-face interviews in six large-scale panel surveys conducted by the University of Michigan's Survey Research Center. The findings suggest that, at least with respect to some types of survey questions, there are declining levels of reliability for questions with greater numbers of words and provide further support for the advice given to survey researchers that questions should be as short as possible, within constraints defined by survey objectives. Findings reinforce conclusions of previous studies that verbiage in survey questions—either in the question text or in the introduction to the question—has negative consequences for the quality of measurement, thus supporting the KISS principle ("keep it simple, stupid") concerning simplicity and parsimony.